The Traces of “New Character” in Uzbek Short Story Heroes Based on Two Examples of Uzbek Short Stories of the Present Day - Veli Savaş Yelok (Gazi Akademik Bakış)
The era following the Uzbek independence resulted in a renaissance in Uzbek life. This process in which a renaissance was experienced, also affected the material and moral elements that shape their view of life. When this situation affected the way people understand life, this reform of the Uzbek people naturally formed “the new era”. This new era demanded new ways of thinking from those who lived in that era. The effect of this development and change on people’s minds and their way of understanding and thinkingand its description found itself in literary life. In the short stories published following the independence, the spirit of the time and the different fates of those people who lived in that era were reflected. As a result, writers created the heroes of today through the change experienced by people in their inner world who lived in the same era as the writers. As a general principle, creating a hero is seen as the first issue in the literature of every era. This is so because the hero in the work of literature is the tool that reflects the inner and outer world of the people of a specific era. All the nice and ugly things in a person’s life -starting from the person’s lifestyle and continuing to the end of his life- are passed onto the hero’s thoughts and actions. Describing the changes constantly observed in a hero’s character, reflecting these by forming a direct relationship with the era is comparatively easier in a short story when compared to other genres. In this article, information on the development of short story in present day Uzbek Literature is presented. In addition, the reflection of “the person of the new era” observed in the heroes in the stories “The Author” and “The Trick of Gumshoe Jacob” written by Erkin A‘zam and Xurshid Dostmuhammad who have gained the admiration of readers in their works following the independence is studied.